2020
DOI: 10.1186/s12888-020-02547-7
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit attachment and the outcomes of acceptance and commitment therapy and cognitive behavioral therapy for depression

Abstract: Background: Attachment theory predicts that patients who are not securely attached may benefit less from psychological treatment. However, evidence on the predictive role of attachment in the effectiveness of treatment for depression is limited. Methods: Explicit attachment styles, levels of attachment anxiety and attachment avoidance, as well as implicit relational self-esteem and implicit relational anxiety were assessed in 67 patients with major depressive disorder (MDD) receiving Acceptance and Commitment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Although there was significantly higher effectiveness for the ACT technique than for BA, the effectiveness of the BA technique was still observed over time, as it reduced all cognitive symptoms even after a two-month interval. This finding is consistent with the research results of Babakhanzadeh et al (18), Melli et al (19), and A-Tjak et al (20).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although there was significantly higher effectiveness for the ACT technique than for BA, the effectiveness of the BA technique was still observed over time, as it reduced all cognitive symptoms even after a two-month interval. This finding is consistent with the research results of Babakhanzadeh et al (18), Melli et al (19), and A-Tjak et al (20).…”
Section: Discussionsupporting
confidence: 94%
“…Melli et al (19) reported that metacognition may have an important role in health anxiety in clinical samples. The effectiveness of ACT in decreasing depressive symptoms was also confirmed (20,21). A-Tjak et al (20) showed that ACT, as well as reductions in avoidant and anxious attachment, predicts symptom reduction after psychological treatment for depression.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For this reason, ACT is part of the newer, "mindfulness and acceptance" wave of behavioral therapies made popular over the past 20 years. As a psychotherapy, ACT is an efficacious treatment for a variety of clinical disorders, including social anxiety (Kocovski et al, 2013;Craske et al, 2014;Herbert et al, 2018), depression (Tamannaeifar et al, 2014;A-Tjak et al, 2018;Pleger et al, 2018), obsessive-compulsive disorder (OCD) (Ghasemi et al, 2017;Rohani et al, 2018;Twohig et al, 2018), chronic pain (Thorsell et al, 2011;Wetherell et al, 2011;McCracken et al, 2013), substance use disorders (Luoma et al, 2012;Lanza et al, 2014;Azkhosh et al, 2016), and others. It is also efficacious when used in non-clinical settings, to help enhance athletic performance (Lutkenhouse et al, unpublished;Gross et al, 2016;Josefsson et al, 2019), to improve workplace performance (Bond and Bunce, 2003;Bond and Flaxman, 2006;Bond et al, 2016), to lessen procrastination in college students (Scent and Boes, 2014;Gagnon et al, 2016;Wang et al, 2017), to serve as a smoking cessation treatment (Hernandez-Lopez et al, 2009;Bricker et al, 2017;O'Connor et al, 2020), and others.…”
Section: Acceptance and Commitment Coaching As A Treatment For Mpamentioning
confidence: 99%